Vocabulary Acquisition in First Language: Can This Be Categorized Under Any Universal Developmental Stages? - Sikder Shafinaz (East European Journal of Psycholinguistics, 2016)
This researched based case study has been conducted to investigate the fact that whether first language acquisition process in case of vocabulary (acquiring word meanings) follows some certain sequential stages despite of specific learners and their particular contexts. That is to say, to challenge the existing idea of having universal developmental patterns in case of vocabulary acquisition which tries to bring all the unique learners under one single umbrella, this study was conducted on an individual to observe whether and to what extent the child is following or conforming up to any idealistic standard of acquiring vocabulary. Therefore the study had some pre-determined questions set which was ask to the randomly selected child within an informal context (her play time). Interestingly, the study results which were analyzed both qualitatively and quantifiably with support of secondary literatures revealed that the child is not following any particular patterns of development at a time.  Rather is developing word meanings by following some random sequences. That is to say, she has developed some features of word meanings which she should have acquired in some later stages (after a particular age) according to the claim of many researchers. On the other hand, she has not yet acquired features which she should have acquired already. Therefore it can be concluded that a child’s first language vocabulary acquisition process (especially acquisition of word meanings) cannot be made generalized under some certain or principled patterns or rules. This is because every learning process is unique since every individual learner is unique.ReferencesCruttenden, Alan. (1985). Language in Infancy and Childhood: A Linguistics Introductionto Language Acquisition. Manchester, Manchester University Press.Dodd, H. David & Tomikawa, A. Sandra (1980). Early Word Meanings: Perceptually orFunctionally Based? Child Development, 51 (4), 1103–1109. Retrieved from:http://www.jstor.org/stable/1129550Mace-Matluck, J. Betty. (1979). Order of Acquisition: Same or Different in First- andSecond-Language Learning? The Reading Teacher, 32 (6), 696–703. Retrieved from:http://www.jstor.org/stable/20194855.Miller, A. George (1978). The Acquisition of Word Meaning. Child Development, 49 (4),999-1004. Retrieved from: http://www.jstor.org/stable/1128739Ritgerd, B. A. (2014). First Language Acquisition: The Rate and Style of VocabularyGrowth in the First Years. Haskoli Islands, 1–26. Retrieved from:http://skemman.is/stream/get/1946/17417/40471/1/BA_Essay.pdfScovel, Thomas. (2004). Psycholinguistics (5th ed.). New York, NY: Oxford UniversityPress Smith, D. Michael. (1978). The Acquisition of Word Meaning: An Introduction. ChildDevelopment, 49(4), 950–952. Retrieved from: http://www.jstor.org/stable/11287338. You, Yunjung. (2011). Factors in Vocabulary Acquisition through Reading. ITJ, 8, 43–57Retrieved from: http: //15524-21995-1-PB.pdf